ANNUAL CUMULATIVE OF SOIL CARBON CHANGE IN Pinus merkusii PLANTATION IN CIANTEN, WEST JAVA - Siringoringo, Harris Herman; Siregar, Chairil Anwar (Indonesian Journal of Forestry Research, 2005)
Important    carbon  storage  in a forest vegetation   includes  below  ground  carbon  storage  and above ground   carbon   storage.    Carbon   storage  under  the ground   is  higher  than  that  above  ground,   so that soils are critical both  as a source  and sink of  carbon.   The  main  objective  of  this research  is to examine the annual  changes  of  soil carbon   storage   from  year 2001   to year 2003 in the permanent   plots  of  an experimental   plantation    (new  plantation   established   in the  year 2001)  and in the  permanent    plots  of control   plot/baseline  (young  secondary  forest),  in Cianten  Experimental    Site, Bogor,  West Java.    Soil carbon content   at 0-30 cm depth   for 0 year old, 1  year old and 2 year old plantations   are 4.14- 9.35%, 4.08  8.83%  and 3.04-   7.61  %, respectively.    Soil carbon  content  at control  plot  for 2001,  2002 and 2003 are 1.86-5.75%,  2.32 - 5.79% and 2.05 - 4.84%,  respectively.    Bulk density   at 0-30 cm soil depth  for 0 year old,  1  year old, and 2 yea.r  old plantations   are 0.38 - 0.5  mg/ m,  0.38 - 0.52%  mg/ m3 and 0.32  - 0.5 mg/ m, respectively.    Bulk density  at control  plot  for 2001,  2002 and 2003 are 0.47 - 0.63  mg/m3,  0.43 -0.6 mg/m3  and 0.4 1- 0.55  mg/m3,  respectively.     The  cumulative   soil carbon   stock  of  Pinus  merkusii plantation   is somewhat   higher  than  that of  baseline in Cianten  Experimental   Site, Bogor, West Java.